Demographic factors influencing tolerance towards LGBT individuals among Malaysians - Hsin Nie, Ling; Ting, Su Hie (Asia-Pacific International University, Muak Lek, Thailand, 2022)
This study examined the influence of demographic characteristics on tolerance towards LGBT in Malaysia. The specific aspects studied were: (1) views on LGBT sexual orientation; (2) views on rights of LGBT individuals; and (3) relationships between demographic characteristics and views on LGBT sexual orientation and rights. Questionnaire data were collected from 413 respondents living in Malaysia (88.1% heterosexuals; 11.9% LGBT). A majority of respondents were degree holders (82.8%) in their twenties (82.3%) and of Chinese descent (71.7%). The results showed moderate tolerance towards LGBT sexual orientation where some respondents felt that heterosexuality is best because of religion and morality, while others believed that people are born with LGBT tendencies and need not keep their sexual orientation a secret. Interestingly, the respondents were receptive towards LGBT rights, including the right to organise public events, adopt a child, and have same-sex marriage. ANOVA results showed that age, ethnic group, religious background, and sexual orientation influenced tolerance towards LGBT sexual orientation and rights. Older individuals, Malay and Sabah indigenous, Muslims, Christians, and heterosexuals seemed to be the least supportive of LGBT. The study suggests that openness towards LGBT is growing among the younger generation.